Economic dependency ratios: present situation and future scenarios - WWWforEurope; Loichinger, Elke; Hammer, Bernhard; Prskawetz, Alexia; Freiberger, Michael; Sambt, Jose (Vienna, 2014)
"In this paper we compare several types of economic dependency ratios for a selection of European countries. These dependency ratios take not only into account the demographic structure of the population, but also the differences in age-specific economic behaviour such as labour market activity, income and consumption. In simulations where we combine patterns of age-specific economic behaviour with population projections, we show that in all countries population ageing would lead to a pronounced increase in dependency ratios if present age-specific patterns were not to change. Our analysis of cross-country differences in economic dependency demonstrates that these differences are driven by both differences in age-specific economic behaviour and in the age composition of the populations. In addition, the specific deffinitions of the ratios will result in different interpretations of dependency. The choice which dependency ratio to use in a specific policy context is determined by the nature of the question to be answered. The comparison of our various dependency ratios across countries gives insights into which strategies might be effective in mitigating the expected increase in economic dependency due to demographic change."